2002
DOI: 10.1038/sj.bjc.6600604
|View full text |Cite
|
Sign up to set email alerts
|

Intakes of fruits and vegetables, carotenoids and vitamins A, E, C in relation to the risk of bladder cancer in the ATBC cohort study

Abstract: We examined the relation between dietary fruit and vegetables, carotenoids and vitamin intakes and the risk of bladder cancer among male smokers in a prospective cohort study. Over a median of 11 years, we followed 27 111 male smokers aged 50 -69 years who were initially enrolled in the Alpha-Tocopherol Beta-Carotene Cancer Prevention Study. During this period, 344 men developed bladder cancer. All of these men had completed a 276-food item dietary questionnaire at baseline. Cox proportional hazards models wer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
90
3
6

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 137 publications
(101 citation statements)
references
References 25 publications
2
90
3
6
Order By: Relevance
“…23,31,32 Cigarette smoking is the most important established risk factor for bladder cancer. 4 The effect of vegetables and fruit intake on the risk of bladder cancer may differ between smokers and non smokers.…”
Section: Discussionmentioning
confidence: 99%
“…23,31,32 Cigarette smoking is the most important established risk factor for bladder cancer. 4 The effect of vegetables and fruit intake on the risk of bladder cancer may differ between smokers and non smokers.…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have previously examined the association between cruciferous vegetable intake and bladder cancer risk (15)(16)(17)(18)(19)(20). However, to our knowledge, only one study (16), published in 1999, reported a statistically significant inverse association (relative risk = 0.49 for the highest versus the lowest cruciferous vegetable consumption; 95% CI, 0.32-0.75, P for trend = 0.008).…”
Section: Cancer Epidemiology Biomarkers and Prevention Cancer Epidemiomentioning
confidence: 99%
“…Only a few epidemiologic studies have investigated the relationship between bladder cancer risk and intake of cruciferous vegetables, with inconsistent findings (15)(16)(17)(18)(19)(20). Not accounting for whether cruciferous vegetables are eaten raw or cooked may partly explain this inconsistency, because cooking may substantially destroy and/or reduce isothiocyanates obtained from cruciferous vegetables, subsequently attenuating the cancer-preventive potential of these vegetables.…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3][4] Failing to demonstrate an inverse relationship between cancer incidence and consumption of the vitamins prominent in these plant products, investigators have turned attention to the many classes of nutrient phytochemical constituents also present in these foods. 5 Specific isoprenoids, culled from a group of some 22,000 products of secondary plant metabolic pathways sharing a common precursor, mevalonic acid, 6 have demonstrated anticarcinogenic and chemoprotective activities.…”
mentioning
confidence: 99%